Redoable Tie-Over Dressing Using Multiple Loop Silk Threads - Hyeon Jong Jo; Jun Sik Kim; Nam Gyun Kim; Kyung Suk Lee; Jae Hoon Choi (Archives of Plastic Surgery, 2013)
After skin grafting, to prevent hematoma or seroma collection at the graft site, a tie-over dressing has been commonly used. However, although the conventional tie-over dressing by suture is a useful method for securing a graft site, refixation is difficult when repeated tie-over dressing is needed. Therefore, we recommend a redoable tie-over dressing technique with multiple loops threads and connecting silk threads. After the raw surface of each of our cases was covered with a skin graft, multiple loop silk thread attached with nylon at the skin graft margin. We applied the ointment gauze and wet cotton/fluffy gauze over the skin graft, then fixed the dressing by connecting cross-counter multiple loop thread with connecting silk threads. When we opened the tie-over dressing by cutting the connecting silk threads, we repeated the tie-over dressing with the same method. The skin graft was taken successfully without hematoma or seroma collection or any other complications. In conclusion, we report a novel tie-over dressing enabling simple fixation of the dressing to maintain proper tension for wounds that require repetitive fixation. Further, with this reliable method, the skin grafts were well taken.